1999
DOI: 10.1001/archopht.117.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Racial Difference in the Incidence of Retinal Detachment in Singapore

Abstract: To determine the incidence of retinal detachment (RD) operations in a multiracial Southeast Asian population. Design: Population-based incidence study using a universal medical savings database in Singapore. Methods: Information on all RD operations performed for rhegmatogenous RD (International Classification of Diseases, Ninth Revision, Clinical Modification code 361.0) between 1993 and 1996 was retrieved and analyzed from a population-wide, government-administered medical savings database. Exudative, tracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
70
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 7 publications
16
70
0
7
Order By: Relevance
“…5 This has been confirmed in our study in both populations with a demand incidence of 4.6 and 2.0 per 100 000 for Wolverhampton and Walsall, respectively (Table 2).…”
Section: Ethnic Demand Incidencesupporting
confidence: 82%
See 2 more Smart Citations
“…5 This has been confirmed in our study in both populations with a demand incidence of 4.6 and 2.0 per 100 000 for Wolverhampton and Walsall, respectively (Table 2).…”
Section: Ethnic Demand Incidencesupporting
confidence: 82%
“…There have been few studies 5,6 analysing racial differences in the incidence of retinal detachment. Wong et al 5 have shown a three-fold higher incidence of retinal detachment in Chinese compared to Indians, and alluded to the cause being the increased prevalence of myopia in Chinese compared to Malays.…”
Section: Ethnic Demand Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…These data are not dissimilar from results in Sweden (10.6:100 000), 8 and Singapore (10.5:100 000). 9 Our calculations underestimate the actual incidences. The profile of private health plans shows that the Southeast Region concentrates 70% of those covered people in Brazil.…”
Section: Discussionmentioning
confidence: 60%
“…Our study found that the incidence of RRD was higher in males than in females, with no marked difference between the sexes in refractive status, which are risk factors of RRD. Ocular trauma was also a risk factor of RRD in males [7,20]. However, traumatic retinal detachment was not included in our study.…”
Section: Discussionmentioning
confidence: 86%